Efficiency of zakat institutions in empowering Ummah / Muhamad Nafik Hadi Ryandono ...[et al.] - Hadi Ryandono, Muhamad Nafik; Widiastuti, Tika; Qulub, A. Syifaul; Cahyono, Eko Fajar; Insani, Taqiyah Dinda (Universiti Teknologi MARA, 2021)
Issue on the efficiency of zakat institutions is important because zakat is an Islamic financial instrument that functions as wealth distribution. This distribution plays a role in empowering ummah, as the provisions related to the attributes of the zakat distribution process have been clearly stated in the Holy Quran and Sunnah. This study aims to analyze the efficiency of zakat institutions in Indonesia. Zakat institutions in Indonesia are categorized in several types based on historical aspects of the establishment of zakat institutions. The instutions are based on government, corporation, zakat management organization and mass organization. By using the Data Envelopment Analysis (DEA) method, this study found that the order of efficiency according to the type is government, corporation, zakat management organization and mass organization. Furthermore, results of this study can be used as a reference by the type of zakat institutions in Indonesia for better improvement. Thus, the potential management of zakat owned by Indonesia could be channeled properly